Growth performance of sweet corn (Zea Mays) on the mineral soil amended with sago waste biochar / Suraiya Mahdian ... [et al.] - Mahdian, Suraiya; Mohidin, Hasmah; Man, Sulaiman; Kanang, Kevin Dinggun; Ali, Azizu Soteh (UiTM Press for the Research Management Center (IRMI), Universiti Teknologi MARA, 2021)
Sago waste is a viable and utilisable resource for conversion into valueadded products. Sago fronds and bark have great potential for use as biochar feedstocks due to their availability and high starchy-lignocellulosic compounds content. However, few studies have been conducted regarding sago waste conversion into biochar. Hence, this study evaluates the viability of converting sago waste into biochar and as a soil amendment for mineral soil planted with sweet corn (Zea mays) plants. The study was located at the Farm Unit, UiTM Samarahan, Sarawak. Five treatment combinations of sago bark (SB) biochar and sago frond (SF) biochar were used in a randomised complete block design (RCBD) with eighty plants per treatment. The procedure was replicated three times. Parameters were measured at harvest 85 days after treatment (DAT), including total dry biomass, cob weight, cob number and cob grade. All the recorded data were statistically analysed by the analysis of variance (ANOVA) using SAS 9.4 (2013). Different treatments showed significant effects for all the parameters studied. The highest values for total dry biomass and cob yield were obtained using SB biochar 100%. The results of this study reveal the potential of SB biochar as an alternative soil amendment to increase sweetcorn biomass and yield.